“Control y monitoreo de la humedad y temperatura mediante un sistema scada para el cultivo de mora en el sector de Yanahurco” - Andagana Paredes, Luis Adrián (2021)
ABSTRACT In this research, a land survey and characterization was carried out terrain located in Yanahurco parish at Tres Juanes place, the property has equipment and implements which were verified to know their usefulness and operation for the technological proposal. Set aut how objective to automate a drip irrigation system was the objective, which is operated by a Siemens KTP 600 screen. The primary reason for the automation of the irrigation system is to control the humidity variable, monitor the soil temperature and water level, reservoir water by orders issued by a programmable logic controller (PLC), the orders allow to automatically manipulate the opening and closing of the solenoid valves that are located on the ground. The equipment is activated when the sensor detects that the humidity is greater than 70% and less than 90%, an interval that is established in the system programming; on the other hand, the temperature is only monitored to visualize the climatic conditions. The irrigation system operation activates the water pumps that generate energy consumption whose electrical magnitudes are displayed on a Sentron Pac 3120 meter. The devices and elements installed in the irrigation system provide information which is stored in a database through an intelligent IOT 2040 gateway. All the equipment and elements installed in the irrigation system allow the user to control and monitor blackberry cultivation, improving production, water resources and electricity consumption